OP55 Evaluating costs of advance care planning; results from the international ACTION study. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Korfage, I; Polinder, S; van der Heide, A; Preston, N; van Delden, J; Miccinesi, G; Lunder, U; Pollock, K; Deliens, L; Groenvold, M; Rietjens, J
Abstract : Background: Systematic evaluation of health care use and costs is important to identify the impact of advance care planning (ACP) programs. Such evaluations are currently scarce in Europe. Methods: Our study was performed in the context of the ACTION trial, a randomized controlled study to evaluate effects of the ACTION Respecting Choices (RC) ACP intervention in patients with advanced cancer in six European countries. We applied a healthcare perspective and identified hospital care use from hospital medical records for 1 year after study inclusion. Unit prices were calculated for all six countries separately. The unit price of the 'Respecting Choices' ACP intervention was determined with the micro-costing method, which is based on detailed assessments of all resources used. Results: Most intervention patients had one ACP conversation, one third had two. The average length was 90 minutes (standard deviation 45 minutes). Unit costs were comparable between countries for most interventions, with the exception of cancer-specific treatment. Most patients received chemotherapy, with a minority receiving surgery. Preliminary analyses showed similar patterns of health care use in both ACP and control groups: numbers of diagnostic procedures such as scans and biopsies were comparable; mean (range) length of hospital stay was 9 days (0 - 63) and 8 days (0 – 75) in intervention and control patients, respectively. Conclusion: Unit costs of health care interventions were remarkably comparable between countries. The ACTION RC ACP intervention, consisting of conversations by patiens, relatives, and facilitators, did not appear to affect hospital care use. Funding: EU FP7.